Principles and Methods of Toxicology - Hayes, A. Wallace; Ed (Informa Health Care, 2008)
Extensively revised and updated with four new chapters and an expanded glossary, this fifth edition provides comprehensive coverage in a manageable and accessible format. The book examines each method or procedure from the standpoint of technique and interpretation of data and discusses problems and pitfalls that may be associated with each.